(untitled) (Academia Science Repository, 2023)
In Uzbekistan, in recent years, there has been a dynamic development of the tourism industry. This is due to the expansion and strengthening of interethnic ties, the country’s integration into the international tourism market, increasing the level of professionalism in promoting the cultural, historical and spiritual heritage of Uzbekistan, and improving the quality of tourist services.